Rate constants for the formation of SiO by radiative association. Issue 2 (8th July 2017) - Cairnie, M.; Forrey, R. C.; Babb, J. F.; Stancil, P. C.; McLaughlin, B. M.
Abstract: Accurate molecular data for the low-lying states of SiO are computed and used to calculate rate constants for radiative association (RA) of Si and O. Einstein A-coefficients are also calculated for transitions between all of the bound and quasi-bound levels for each molecular state. The radiative widths are used together with elastic tunnelling widths to define effective RA rate constants which include both direct and indirect (inverse pre-dissociation) formation processes. The indirect process is evaluated for two kinetic models which represent limiting cases for astrophysical environments. The first case scenario assumes an equilibrium distribution of quasi-bound states and would be applicable whenever collisional and/or radiative excitation mechanisms are able to maintain the population. The second case scenario assumes that no excitation mechanisms are available which corresponds to the limit of zero radiation temperature and zero atomic density. Rate constants for SiO formation in realistic astrophysical environments would presumably lie between these two limiting cases.